Multisystemic eosinophilic epitheliotropic disease in a horse - Thielemann, Lauren; Lui, Clinson; McAda, Wesley; McAda, Reagan; Jennings, Alexis; Coleman, Michelle C.; Bryan, Laura (Brazilian Journal of Veterinary Pathology, 2024)
Clinical History: A 16-year-old paint mare presented to the Texas A&M equine emergency medicine service for chronic weight loss despite an adequate appetite, inappropriate mentation, and hair loss. Clinical signs started three months prior with a history of gradual weight loss that did not respond to prophylactic oral deworming, diet change, or dental float. The horse then began displaying signs of pruritus with self-inflicted patchy alopecia primarily localized to the pigmented skin followed by rapid epaxial and gluteal muscle atrophy and fluctuant swelling around the head and neck (Fig. 1). Palpable, firm skin nodules appeared in the cervicothoracic, pectoral, axillary, and inguinal regions (Fig. 2). The mare also began exhibiting signs of colic, decreased borborygmi and dry fecal matter. Despite an initial two-day improvement with gastric decompression, anti-inflammatory medications, and supportive care, the horse became acutely neurologic with abnormal mentation and right front limb lameness/paresis.